Optimal placement and sizing of DG and DSTATCOM in order to mitigate power losses in electrical distribution system - Mahanta, Smrutirekha; Maharana, Manoj Kumar (Institute of Advanced Engineering and Science, 2025)
The emphasis is now shifting away from conventional methods of power generation and towards unconventional distributed energy resources (DERs) located at distribution voltage level due to the rapid depletion of fossil fuel supplies and significant environmental pollution. Emphasis on research into the applications of DERs found scope in microgrids and active distribution networks. The placement of DERs close to load centers aids with providing clean, reliable power to additional customers, reduce electricity losses along transmission and distribution lines and in event of faults it allows to operate in islanded mode. This manuscript focuses on power smoothing, which implies reduction of power loss, improved voltage levels, and voltage stability. This study aims to optimize the capacities and placements of distributed generations (DGs) and distribution static compensators (DSTATCOMs) in order to reduce real power loss and improve the voltage profile. The problem of voltage from undistributed energy resources can best be solved by DSTATCOM. The goal function of the direct load flow technique, which also makes use of voltage deviation and the loss sensitivity factor, is used in this study to pinpoint the ideal placement for the DG and DSTATCOM on the MATLAB platform. The method is tested using the 33 and 69 bus routes. When the results are compared to recent methodologies, they show encouraging results.